CFD modelling development and experimental validation of a phase change material (PCM) heat exchanger with spiral-wired tubes. (1st February 2018) - Youssef, W.; Ge, Y.T.; Tassou, S.A.
Highlights: Phase change materials (PCMs) for latent heat storage is important to a solar thermal application. The use of PCM in solar thermal is quite limited due to the poor thermal conductivity. A novel heat transfer enhancement method has been proposed and modelled with CFD. The CFD temperature variations and visualizations of the PCM are presented. The effects of inlet heat transfer fluid parameters on the PCM performance are demonstrated. Abstract: Employing phase change materials (PCMs) for latent heat storage (LHS) application has a great potential to improve a solar thermal system performance. Despite this fact, the use of PCM in this area is quite limited due to the poor thermal conductivity of available PCMs. Therefore, heat transfer enhancement is one of the essential strategies that can overcome this obstacle. In this paper and related project, a PCM heat exchanger (HX) is purposely designed with spiral-wired tubes and integrated in an indirect solar assisted heat pump test system. Although the spiral-wired tube has not been applied in a PCM HX, it is expected to enhance significantly the PCM heat transfer and heat storage performance. To verify this and understand the PCM heat storage and releasement processes, a detailed 3D CFD model has been developed for the PCM HX and validated with measurements. The temperature variations and visualizations of the PCM during charging and discharging processes are therefore simulated and presented temporally. Furthermore, the effects of different inlet heat transfer fluid flow rates and temperatures on the PCM melting/solidification time are demonstrated in this study. Some significant simulation results have been obtained which can instruct efficiently the operation of the heat exchanger and its integration with the solar system.